Sustainability Dimensions of Gedong Gincu Mango Farming: a Case Study in Majalengka Regency, West Java Province, Indonesia - Sulaksana, Jaka; Marina, Ida; Saputra, Febrian; Hidayat, Yayat (Anuário do Instituto de Geociências, 2025)
This study aims to analyze the sustainability status of the gedong gincu mango agribusiness in Majalengka Regency and identify the factors that influence it. Using a quantitative descriptive method with Multidimensional Scaling (MDS) analysis, this study involved a survey of farmer groups, academics, government, and extension workers. The results of the analysis showed that overall, the status of agribusiness sustainability in the village was classified as moderately sustainable with an average index value of 70.9%. The ecological dimension has the highest index value (78.3%), while the technological dimension has the lowest index value (57.8%). It indicates that the environmental aspect is well maintained, but there is a need for improvement in the application of agricultural technology. The sustainability of the gedong gincu mango agribusiness is influenced by various complex interrelated factors, including social, economic, institutional, technological and environmental factors. To achieve optimal sustainability, a comprehensive approach involving all stakeholders is required. Monte carlo analysis result has shown that the model is good enough, also stress and R-square.